Selective Immunoreactivity for WT1 Carboxy-Terminus Distinguishes Desmoplastic Small Round Cell Tumor From its Histologic Mimics. (September 2022) - Wong, Yin Ping; Buckley, Kaila; Iwenofu, O. Hans; Singhi, Aatur; Kahwash, Samir B.; Arnold, Christina A.; Tan, Geok Chin; Arnold, Michael A.
Desmoplastic small round cell tumor (DSRCT) is an aggressive pediatric round cell sarcoma containing a characteristic EWSR1-WT1 gene fusion. In the absence of genetic data, distinguishing DSRCT from other small round cell tumors of childhood can be problematic due to overlapping histologic and immunohistochemical features. We studied the utility of immunohistochemistry with antibodies targeting both the amino-terminal and carboxy-terminal regions of the Wilms tumor-1 (WT1) protein in differentiating these groups of tumors. The study cohort included 33 cases of genetically confirmed pediatric round cell tumors (10 DSRCTs, 12 Wilms tumors, 10 Ewing sarcomas, and 1 CIC -rearranged sarcoma). Immunoreactivities and immunolocalization of both the WT1 amino-terminus and carboxy-terminus were scored and documented. All DSRCTs displayed selective reactivity for only the WT1 carboxy-terminus (10/10), while dual immunoreactivity for both the WT1 carboxy-terminus (12/12) and amino-terminus antibodies (12/12) were characteristic of Wilms tumors. CIC -rearranged sarcoma showed variable WT1 nuclear immunopositivity (1/1, 1/1) and Ewing sarcomas were consistently WT1-negative for both the WT1 amino-terminus (0/10) and carboxy-terminus (0/10). Dual WT1 amino-terminus and carboxy-terminus immunohistochemistry remains a helpful diagnostic tool in discriminating intraabdominal small round cell tumors, which serves as an adjunct to the genetic information in preventing misdiagnosis.